A Crisis of Executive Managerialism in the EU: No Alternative? - Joerges, Christian; Weimer, Maria (Social Science Research Network, 2012)
Against a backdrop of rapidly evolving crisis management in the European financial and sovereign debt crisis this essay aims both to explore and to re-consider the role of law in the EU integration process: What did law accomplish? Where did it fail? What is law going to endure? What kind of future can it envisage? The essay traces back the evolution of the law-politics relationship in both EU legal scholarship and practice from the foundational period of ‘integration-through-law’ to the advent of ‘new governance’ in the EU, and finally to the current deep transformations of EU law in new economic governance and the financial crisis. The centrality of law as ‘both the object and the agent’ of European integration, and the legal enshrinement of EU’s economic constitution has recently neglected the weight of ‘the social’ in the societies of post-war Europe, a failure which was to become detrimental to both domestic social stability and the legitimacy of integration. Attempts to cure Europe’s social deficit by re-conceptualizing the notion of law as new governance have widened the theoretical perspective of EU legal scholarship. Yet new governance has not delivered more social democracy and justice in Europe in practical terms, and continues to suffer from the methodological problems of its ‘definition-by-contrast.’ These problems re-emerge in current new economic governance, which Europe’s crisis management is generating. This hybrid arrangement of hard and soft law instruments has, to date, been economically unsuccessful and socially disastrous, especially in the South of Europe. Equally disquieting, the notion of democratic law (either in traditional or experimentalist understandings) has been replaced by a praxis of authoritarian executive managerialism. The essay concludes by sketching out an alternative understanding of law-mediated legitimacy in the integration process, namely ‘conflicts-law constitutionalism’. This approach stresses the normative value of conflicts and pluralism in the process of European integration. Instead of ‘ever more Europe’ it aims to secure the existing democratic credentials of EU law, namely its ability to correct the democratic deficit of the Member States while respecting their constitutional integrity.
Law
Keywords: EU economic constitution; EU financial crisis; European Union; governance; unity in diversity

Polanyi's Embeddedness and Shareholder Stewardship: A Contextual Analysis of Current Anglo-American Perspectives on Corporate Governance - Talbot, Lorraine E. (Social Science Research Network, 2012)
Polanyi saw the economy as properly embedded in society and argued that the capitalist free market, in commodifying social relations of production, seeks to disembed the economy from society. The resulting lack of continuity between society and economy, he maintained, created conflict which necessarily required state intervention. The market economy, therefore, in contrast to neoclassical/neoliberal economics’ vision of an autonomous, self-regulating market, required more, not less, state intervention to sustain it than alternative, more embedded economies. This article explores this conflict in the context of a specific neoliberal claim: that institutional shareholders are capable of being good “stewards” of the companies in which they invest. Utilising Polanyi’s embeddedness, this article assesses the “stewardship” approach as it is manifested in the US and in the UK. This approach is posited on a vision of a disembedded, self-regulating market. Putting it into practice is thus a retrograde step which will only exacerbate the problems created by the market-based corporate governance strategies which have prevailed since the late 1970s onwards.
Law
Keywords: Polanyi; conflict; crisis; embeddedness; shareholder stewardship

Karl Polanyi E O ‘Grande Debate’ Entre Substantivistas E Formalistas Na Antropologia Econômica (Karl Polanyi and the 'Great Debate' Between the Substantivists and Formalists in Economic Anthropology) - Machado, Nuno Miguel Cardoso (Social Science Research Network, 2012)
Na raiz do pensamento Polanyiano, encontra-se a distinção entre economia no sentido substantivo e economia no sentido formal. Com efeito, a concepção substantivista que define a economia como um processo instituído de interação entre o homem e o ambiente natural e social que o rodeia e resulta em contínua oferta de meios para satisfazer as necessidades humanas constitui a base do método preconizado pelo autor: a análise institucional. Com tal distinção, Polanyi (1977a) pretende evitar a "falácia economicista" que consiste na identificação automática da economia com sua forma de mercado. Ao contrário, só na moderna economia capitalista é que um "sistema de mercados formadores de preços" desempenha papel fundamental. Essas questões foram alvo de um "Grande Debate" entre as correntes substantivista – encabeçada por Polanyi – e formalista no contexto da disciplina da Antropologia Econômica.At the root of Polanyian thought, a distintiction can be found between the substantive and formal concepts of the economy. In fact, the substantivist conception, that defines the economy as an instituted process of interaction between man and its natural and social environment, which results in a continuous supply of material means to meet human needs, constitutes the basis of the method recomended by the author: institutional analysis. With this distinction, Polanyi intends to avoid the "economistic fallacy", which consists of the automatic identification of the economy in its market form. Only in the modern capitalist economy does a system of "price-making markets" play a fundamental role. These questions were amply discussed in the so-called "Great Debate" between the substantivist and formalist schools of thought in the discipline of Economic Anthropology. in Economia e Sociedade, Vol. 21, No. 1 (44), pp. 165-195
Sociology; Anthropology
Keywords: economy; formalism; institutional analysis; market; substantivism